Mass-spectrometric research of ion sputtering processes at high primary ion energies - V.A. Baturin; S.A. Yeryomin (Журнал нано- та електронної фізики)
The article is devoted to mass-spectrometric investigation of ion sputtering processes in a wide range of primary ion energies. For this purpose a design of the secondary neutral mass-spectrometer is developed, which unlike the traditional devices of the given type is produced on the base of ion implanter that generates ion beams with energies up to 170 keV and current density on the target up to 1 mA/cm2. Computer simulation of the electron and positively charged ion trajectories in sputtered particle detection system is performed and the optimal parameters of a system for three modes of operation are determined. The emission of sputtered neutral copper clusters and the preferential sputtering processes of molybdenum isotopes at different parameters of the primary ion beam are studied.